1985
DOI: 10.1139/v85-593
|View full text |Cite
|
Sign up to set email alerts
|

Design and reactivity of organic functional groups—utility of imidazolylsulfonates in the synthesis of monobactams and 3-amino nocardicinic acid

Abstract: The imidazolylsulfonate group has been found to be a versatile leaving group in the intramolecular cyclization of p-methoxyphenyl amides and related derivatives of N-substituted L-serine to give the corresponding β-lactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Eventually, we found that diazepanone 21 can be selectively produced, with negligible formation of 22, by employing sulfuryl diimidazole, a seldom used reagent developed by Hanessian as a substitute for the classical Mitsunobu reagent. 24 By using the modified conditions, a library of 12 compounds having the general structure 21 was prepared by varying three diversity inputs including the sulfonyl, aldehyde and isocyanide groups. The only limitation is that aromatic isocyanides cannot be employed in this process.…”
Section: Methodsmentioning
confidence: 99%
“…Eventually, we found that diazepanone 21 can be selectively produced, with negligible formation of 22, by employing sulfuryl diimidazole, a seldom used reagent developed by Hanessian as a substitute for the classical Mitsunobu reagent. 24 By using the modified conditions, a library of 12 compounds having the general structure 21 was prepared by varying three diversity inputs including the sulfonyl, aldehyde and isocyanide groups. The only limitation is that aromatic isocyanides cannot be employed in this process.…”
Section: Methodsmentioning
confidence: 99%
“…Thus we chose to employ the combination of sulfonyl diimidazole (SDI) with NaH. This methodology was first introduced by Hanessian . Although it is, surprisingly, seldom employed, it was already demonstrated by us[12b] to be an useful alternative to the classical Mitsunobu conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hydroxyl group of N-arylamides, as well as peptide analogues,c an be activatedb yc onversion to an imidazolyl sulfonate. [85] Subsequent base-induced ring closure delivers the desired b-lactams in good yields (63-85 %).…”
Section: N1àc4 Cyclizationmentioning
confidence: 99%